The effect of anxiety on the ability to learn gymnastic skills: A study based on the schema theory - Ariza-Vargas, L.; Lopez-Bedoya, J.; Dominguez-Escribano, M.; Vernetta Santana, M. (The Sport Psychologist, 2011)
The objective of this study has been to analyze the effect of anxiety on the level of learning of gymnastics skills, considering two types of practical strategy. The first, derived from Schmidt`s Schema Theory (1975) and termed Teaching Programs, is representative of the hypothesis of variability in practice (Moxley, 1979) and the other strategy, known as Technical Progressions, is derived from more restrictive models of the motor program and is related to the hypothesis of specificity. The sample group (n = 108) was made up of 54 boys and 54 girls, aged between 11and 13, with no previous experience in performing skills related to gymnastics. A 3 × 3 x 2 factorial design of the independent steps was used (Practical Strategy x Trait Anxiety x Gender)—this was a fixed model, with a control group in factor A. The results showed that the main effects on the Learning Level were generated by the areas of Practical Strategy and Trait Anxiety, although their impact was lessened by the functional structure of the skills required. Trait Anxiety is shown to be the main predictor of State Anxiety levels.